Analysis of Cambridge Curriculum Implementation in Mathematics Learning in Indonesia: A Systematic Literature Review - Riza, Muhammad; Slamet, Isnandar; Pramudya, Ikrar (Al-TA'DIB: Jurnal Kajian Ilmu Kependidikan, 2025)
This study systematically reviews research on implementing the Cambridge curriculum in Indonesian institutions, focusing on mathematics learning. Using a systematic literature review (SLR) of 18 articles, results highlight qualitative methods, predominantly descriptive and evaluative approaches, with case studies comprising 28%. Data collection frequently involves observations, interviews, documentation, and Google Form questionnaires. Participants mainly include educators, students, guardians, and principals. Most research targets junior high schools, with less attention to elementary and senior levels. The Cambridge curriculum promotes active learning, critical thinking, and global perspectives, often integrated with Indonesia's national curriculum. Benefits include enhanced English proficiency, global awareness, and modern teaching methods. However, challenges arise from language barriers and limited English-speaking environments. The review identifies key trends and gaps, providing recommendations for future research and practical application.